2018
DOI: 10.1016/j.schres.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Theory of mind impairment and its clinical correlates in patients with schizophrenia, major depressive disorder and bipolar disorder

Abstract: Background: Although Theory of Mind (ToM) impairment has been observed in patients with a wide range of mental disorders, the similarity and uniqueness of these deficits across diagnostic groups has not been thoroughly investigated. Methods: We recruited 35 participants with schizophrenia (SCZ), 35 with bipolar disorder (BD), 35 with major depressive disorder (MDD), and 35 healthy controls in this study. All participants were matched in age, gender proportion and IQ estimates. The Yoni task, capturing both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 54 publications
3
27
1
Order By: Relevance
“…We demonstrated that age of onset was negatively correlated with total DEToMS score and metaphor, also first order belief test was negatively correlated with number of hospitalisations and number of manic/mixed episodes. This is contrary with the results of the Inoue et al's study which showed no correlation between age of onset, duration of illness and first and second order false beliefs 3 28 . Also, we found some clinical variables may be predictor for ToM, therefore for social cognition.…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…We demonstrated that age of onset was negatively correlated with total DEToMS score and metaphor, also first order belief test was negatively correlated with number of hospitalisations and number of manic/mixed episodes. This is contrary with the results of the Inoue et al's study which showed no correlation between age of onset, duration of illness and first and second order false beliefs 3 28 . Also, we found some clinical variables may be predictor for ToM, therefore for social cognition.…”
Section: Resultscontrasting
confidence: 92%
“…There are different results for the correlation of psychotic episodes and ToM and we could not demonstrate any relationship 7,21 . Wang et al research results revealed that second order beliefs test was associated wih psychotic and depressive symptoms 28 . Also, we found some clinical variables may be predictor for ToM, therefore for social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 studies were included (27 full paper and 3 theses) in this meta-analysis. The sample was heterogeneous regarding BD type, 12 studies included only BD I patients, 2 studies included only BD II patients (Ibanez et al, 2012, 2014), 12 studies included both types (BD I and II) and 4 studies did not mention type of BD in their sample (Dalkner et al, 2019; Goitia et al, 2017; Kerr et al, 2003; Wang et al, 2017). For more information, see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have used novel tasks aimed at assessing more specific ToM deficits (Feyerabend et al, 2018; Montag et al, 2010). It is necessary to adapt assessments making them more applicable and specific for BD patients, given that the impairments in BD tend to be more subtle when compared to other populations, such as schizophrenia (Lee et al, 2013; Wang et al, 2017). Finally, further studies should include, in parallel to ToM tasks, a comprehensive neuropsychological battery, making it possible to investigate the relation between cognitive function and ToM performance.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of individual ToM abilities continues to be of interest in current mental health research, since its deficits impact people suffering with schizophrenia, 32 bipolar affective disorder, 33 addictive pathologies, 34 and depressive disorders, 35 alongside other general medical conditions, such as Parkinson’s disease. 36 Recent studies have shown that in people suffering with a chronic depressive illness, both, the cognitive and the affective components, are deficient, 37 and that a flawed individual ToM might be the culprit for the psychosocial and functional deficits associated with a poor mental health. 17 , 38 …”
Section: Discussionmentioning
confidence: 99%